Analisis Faktor-Faktor yang Menentukan Efektivitas Sistem Informasi pada Organisasi Sektor Publik (Survei pada RS Nirmala Suri) - Faj'rin, Oshin Nia Arum; , Dr. Erma Setiawati, Ak., MM., CA (2015)
This objective of this study is to analyze the effect of top management, information system management, user satisfaction, organization culture and information system use of the information system effective. The study is used survey method with primary data obtained questionnaires. The population of this study is all staff in RS Nirmala Suri Sukoharjo. Sample of this study is staff who used information system with 50 respondents. The sampling technique is used convenience sampling. This study were analyzed by using multiple regression. The result of this study share that top management and information system use are statistically significant influence to information system effectiveness while information system management, use satisfaction and organization culture are insignificant influence to information system effevtiveness. Keyword : top management, information system management, use satisfaction, organization culture and information system use.